2012
DOI: 10.1111/j.1365-2699.2012.02753.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the Vipera ursinii complex (Viperidae): mitochondrial markers reveal an east–west disjunction in the Palaearctic region

Abstract: Aim  The aim of this study was to elucidate the phylogeographical pattern of taxa composing the Vipera ursinii complex, for which the taxonomic status and the dating of splitting events have been the subject of much debate. The objectives were to delimit potential refugia and to date splitting events in order to suggest a scenario that explains the diversification of this species complex. Location  Western Europe to Central Asia. Methods  Sequences of the mitochondrial cytochrome b and NADH dehydrogenase subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 46 publications
8
58
1
3
Order By: Relevance
“…The presence of a new distinct lineage, more related to the Caucasian vipers, strongly suggests an additional, more recent, colonization of western Europe (from the V. kazankovi complex or during the split between the V. kaznakovi complex and V. ursinii complex) than the one involving the V. berus group, and possibly one that was concurrent with that of V. ursinii (Early Pliocene; Ferchaud et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a new distinct lineage, more related to the Caucasian vipers, strongly suggests an additional, more recent, colonization of western Europe (from the V. kazankovi complex or during the split between the V. kaznakovi complex and V. ursinii complex) than the one involving the V. berus group, and possibly one that was concurrent with that of V. ursinii (Early Pliocene; Ferchaud et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, these evolutionary units could also have taxonomic value (e.g. identification of taxonomic structure like in Sicista subtilis, Cserkész et al 2015a, b; the ''near to extinction'' taxa of the Nannospalax leucodon superspecies, Németh et al 2013, species within the Vipera ursinii complex, Ferchaud et al 2012;Gvozdik et al 2012;Zinenko et al 2015, or presumable subspecies such as in Cheilotoma musciformis and Coraebus elatus; Kajtoch et al 2013Kajtoch et al , 2014a.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…Recent phylogeographical studies of different animal taxa (e.g. Kry stufek et al 2007;Previ si c et al 2009;Ferchaud et al 2012) revealed that the 'refugia within refugia' concept (G omez and Lunt 2007), originally described for the Iberian Peninsula, is also valid for the Balkans. However, although the Balkan region is richer in species and palaeoendemics in comparison with the Iberian and Apennine peninsulas, the number of phylogeographical studies (particularly comparative ones) of Balkanic fauna is still scarce (Hewitt 2011).…”
Section: Introductionmentioning
confidence: 99%